New fears for food emerging diseases - Friedman, Gayle; Cambridge Educational (Lawrenceville, NJ : Cambridge Educational, 2006)
This program answers those and the other questions as it sheds light on this emerging group of food-borne diseases. Chronic wasting disease, Norwalk virus and bovine tuberculosis are also addressed
Title from title screen
Editor, Jadi Gonska ; music, Yessian Music ; videographer, David Isern
Host: Gayle Friedman
Keywords: Foodborne diseases; Chronic waste disease; Norwalk family; Tuberculosis in cattle